2013
DOI: 10.4239/wjd.v4.i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between sitagliptin and nateglinide on postprandial lipid levels: The STANDARD study

Abstract: Sitagliptin significantly improves some lipid parameters while having a comparable effect on blood glucose to nateglinide. A large-scale prospective study of sitagliptin therapy is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…A reduction in total serum triacylglycerol and chylomicrons was observed, reflecting reductions in chylomicron apolipoprotein B-48 (Apo B-48) and chylomicron cholesterol. The effect on Apo B-48 was later shown not to be due to improved glucose control with sitagliptin [85]. More recently it was shown that a single oral dose of sitagliptin reduces the production of intestinally derived Apo B-48-containing lipoprotein particles in healthy men [86].…”
Section: Extrapancreatic Effects On Lipid Metabolismmentioning
confidence: 96%
“…A reduction in total serum triacylglycerol and chylomicrons was observed, reflecting reductions in chylomicron apolipoprotein B-48 (Apo B-48) and chylomicron cholesterol. The effect on Apo B-48 was later shown not to be due to improved glucose control with sitagliptin [85]. More recently it was shown that a single oral dose of sitagliptin reduces the production of intestinally derived Apo B-48-containing lipoprotein particles in healthy men [86].…”
Section: Extrapancreatic Effects On Lipid Metabolismmentioning
confidence: 96%
“…Multiple studies in normoglycemic, glucose-intolerant, and diabetic human subjects have demonstrated that DPP4 inhibitors reduce postprandial levels of apoB48containing lipoproteins, plasma triglyceride, and circulating free fatty acids (201,202). Furthermore, kinetic studies in healthy nondiabetic human subjects studied under pancreatic clamp conditions demonstrated that sitagliptin reduced the production rate of apoB48 lipoproteins, with no effect noted on the production or clearance of ApoB100 (203).…”
Section: Dpp4 and Control Of Intestinal Lipoprotein Secretion: Preclimentioning
confidence: 99%
“…12,17,18 The data from the current study provided evidence that both nateglinide and acarbose improved fasting and postprandial TG levels within a short period of time (2-week treatment course). It is notable that blood glucose, as assessed by MBG, and body weight were significantly decreased after treatment.…”
Section: Discussionmentioning
confidence: 63%
“…8 However, the effects of nateglinide and acarbose on lipid profiles remain inconclusive. [9][10][11][12][13] Moreover, only a few have conducted a direct comparison between the two agents. 14,15 Therefore, the current study sought to evaluate the effects of nateglinide versus acarbose on both fasting and postprandial lipid profiles in antihyperglycemic agent-naive patients with T2DM.…”
Section: Introductionmentioning
confidence: 99%